Where is the mud from the Fundão dam (Mariana, Minas Gerais state)? e distribuition of tailings along the river valleys affected by the disaster of Samarco/Vale/BHP. (Revista Espinhaço, 2022)
After the collapse of a dam with more than 60 million m³ of iron tailings, a huge debris and mud flow changed the morphology and morphodynamics of downstream fluvial valleys. Part of the tailings traveled to the Atlantic Ocean, but a large volume is still settled on the valleys bottom of the Doce river watershed. However, where did these sediments settle? A brief answer would point out that the closer to the dam, the wider the deposits. But it is not what we see on the field. Knickpoints as waterfalls, rapids, and confluences play an important role to control the river energy, and so, the depositional zones. is paper aims to show the relationship between the widthof tailings deposits through the valleys affected by the Fundão Dam Break (Mariana, MG, Brazil) and rivers' geomorphological profile. We used a topographic approach, based on radar data and satellite images, associated with field excursions to interpret the longitudinal tailings distribution. e results reinforce the relevance of knickpoints to comprehend the tragedy, and the fragility of automatic and simplistic models to predict the effects of dam breaks.
Keywords: Anthropogeomorfology; mining; base level; MarianaMG